2016
DOI: 10.1039/c6ew00237d
|View full text |Cite
|
Sign up to set email alerts
|

Impact of acclimation methods on microbial communities and performance of anaerobic fluidized bed membrane bioreactors

Abstract: Granular activated carbon was acclimated to different substrates, and then used in an anaerobic fluidized bed membrane bioreactor (AFMBR) to treat diluted domestic wastewater. Acetate acclimation produced the best results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…They found that coated membrane had higher organic removal efficiency and achieved higher fouling mitigation performance when GAC particles were fluidized. Various fluidizing solid materials, namely activated carbon [36,44,52,66], glass beads [68], silica [43], and polyethylene terephthalate (PET), have been used in AFMBR reactors. Granulated active carbon (GAC) and powdered activated carbon (PAC) have been mostly utilized due to higher mechanical scouring efficiency and pollutant removal capacity.…”
Section: Afmbr Configurationsmentioning
confidence: 99%
See 3 more Smart Citations
“…They found that coated membrane had higher organic removal efficiency and achieved higher fouling mitigation performance when GAC particles were fluidized. Various fluidizing solid materials, namely activated carbon [36,44,52,66], glass beads [68], silica [43], and polyethylene terephthalate (PET), have been used in AFMBR reactors. Granulated active carbon (GAC) and powdered activated carbon (PAC) have been mostly utilized due to higher mechanical scouring efficiency and pollutant removal capacity.…”
Section: Afmbr Configurationsmentioning
confidence: 99%
“…Li et al (2017) examined the effect of increased benzothiazole on IAFMBR performance and found that biogas production steadily decreased with the increase in benzothiazole concentration, but methane yield was stable at around 0.31 m 3 CH 4 /kgCOD removed [67]. Interesting results were reported by LaBarge et al (2016) for the treatment of domestic wastewater at ambient temperature [52]. Researchers applied four different acclimation methods on GAC and found that the acclimation of GAC communities to acetate substrate considerably enhance organic removal performance.…”
Section: Treatment Of Organic Mattersmentioning
confidence: 99%
See 2 more Smart Citations